Multivariate Analysis of Amazonian Rivers Located in an Area of Intense Industrial Activity, Barcarena, Pará State, Brazil - Iris Danielly da Silva Lopes; Adaelson Campelo Medeiros; Nuno Filipe Alves Correia de Melo; Marcelo de Oliveira Lima; Maria de Lourdes Souza Santos (Journal of Water, 2021)
In this study, were multivariate analysis of the waters of the Arienga and Murucupí rivers located near an area of intense industrial activity in the Barcarena City, Pará State, Brazil. Were analyzed the variables temperature, pH, total dissolved solids, electrical conductivity, DO, BOD, ammoniacal-N, nitrite-N, nitrate-N, phosphate, sulfate and total hardness in four sampling campaigns in the year 2011. This amazon rivers presented physicochemical characteristics well heterogeneous, but similar behaviors for the variables pH, temperature and DO in the extensions evaluated, that is, increase in the source-mouth direction, with variations from 4.77 to 7.33 and 5.51 to 7.3, 25 to 31°C and 27 to 32°C and from 4.4 to 7.98 mg.L-1 and 1.17 to 6.55 mg.L-1 for the Arienga and Murucupi rivers respectively. In addition to these characteristics, the Arienga River also presented an increase for ammoniacal-N, nitrite-N, nitrate-N and hardness in the dry period, with variations from 0.014 to 6.336 mg.L-1, 0.005 to 0.334 mg.L-1, 0.009 to 4.818 mg.L-1 and 1.146 to 14.389 mg.L-1 respectively. In general, Murucupí River presented different physicochemical characteristics that are coherent with the local scenario, where the launch domestic effluents and the environmental impacts caused by industrial waste are visible and recurrent respectively.
Keywords: Multivariate analysis